809Sodium/potassium ratio change was associated with blood pressure change: finding from health check-up data. (2nd September 2021) - Kogure, Mana; Nakaya, Naoki; Hirata, Takumi; Tsuchiya, Naho; Nakamura, Tomohiro; Narita, Akira; Suto, Yoko; Honma, Yoko; Sasaki, Hidemi; Miyagawa, Ken; Ushida, Yusuke; Ueda, Hiroyuki; et al.
Abstract: Background: The sodium (Na)/potassium (K) ratio was reported to be associated with blood pressure (BP). Recently, the Na/K ratio self-monitoring device using spot urine was established. We assessed whether the urinary Na/K ratio change measured using the Na/K device was positively associated with BP change in a health check-up setting. Methods: We targeted 12, 890 participants who attended the annually health check-up in Tome City, Miyagi Prefecture, Japan between 2017 and 2018. Tome city introduced urinary Na/K ratio measurement during health check-up since 2017. We assessed the relationship between change in urinary Na/K ratio and BP change using multiple regression analyses adjusted for age, sex, and change in body mass index (BMI) and alcohol intake. For each year, we compared the baseline characteristics according to the urinary Na/K ratio and BP level. Results: The change in systolic BP and diastolic BP was positively associated with the change in urinary Na/K ratio. The average urinary Na/K ratio was significantly lower in 2018 than in 2017 (5.4±3.0 to 4.9±2.2, p < 0.01). Moreover, their systolic BP in 2018 (130.9±17.4 mmHg) was lower than that in 2017 (132.1±17.9 mmHg) (p < 0.01). Conclusions: The positive association of change in urinary Na/K ratio with hypertension and change in systolic and diastolic BP can be explained by a change in alcohol intake, BMI, and urinary Na/K ratio. Key messages: Measuring the urinary Na/K ratio in community settings is a potential population approach for counteracting hypertension.